Antibiotic prescription before and after rapid antigen detection test (RADT) for beta-hemolytic streptococci - Derhem, Baki; Özsarı, Süleyman; Erturhan, Selman (The European Research Journal, 2019)
Objectives: Acute pharyngo-tonsillitis is one of the diseases that pediatricians and general practitioners most frequently experienced and only a small percentage of patients (20%-30% of pediatric patients, even less in adults) are actually suffering from pharyngo-tonsillitis by group A beta-hemolytic Streptococcus (GABHS). Also three quarters of pharyngitis patients have been treated with inappropriate antibiotics even these patients have viral infections. The aim of this study was to assess the effectiveness of the rapid antigen detection test (RADT) on the percentage of antibiotic prescriptions amongst patients with sore throat at a primary health care center in rural area.Methods: Retrospective Cohort Study was designed to compare antibiotic prescription in patients with sore throats in two groups, one with the use of RADT and other with the clinical desicions of physicians. The x2 test was used between two nominal variables to assess the impact of RADT on antibiotic prescription. For comparison of more than two independent variables, the ANOVA test was used and to identify the differences between groups, the Post-Hoc test was processed.Results: Of the 580 patients, the avarage age of the study population was 25.8 years old while the median age was 21 years (min.=3, max.=65). There was a significant difference between two groups who had tested with RADT or not in terms of antibiotic prescription (p < 0.001). There was a significant difference between 3-14 years of age and 15-44 years of age (p = 0.001) as well as 3-14 years of age and 45-65 years of age (p = 0.009), however there was no significant difference between 15-44 and 45-65 years of age (p = 1.00).Conclusions: Using the RADT is truly effective in reducing the percentage of antibiotic prescriptions in our setting. We believe that, the tools like RADTs which are quickly results and easy to use are really useful in practising (particularly in rural area).